Induced cytomictic diversity in maize (Zea mays L.) inbred - Prashant Kumar Rai; Girjesh Kumar; Avinash Tripathi (Цитология и генетика, 2010)
Mutation breeding has been used for improving oligogenic and polygenic characters, disease resistance and quantitative characters including yielding ability. The cytological stability of maize inbred lines is an important consideration in view of their extensive use in genetics and plant breeding research. Investigation in Zea mays L. confirms that the migration of chromosomes is a real event that cannot be misunderstood as an artifact produced by fixation or mechanical injuries.